Hubungan Antara Dukungan Sosial Dengan Kesiapan Kerja Siswa SMK - Utami, Anita Setyo, Achmad Dwityanto, S.Psi, M.Si (2016)
The amount of unemployement in Indonesia will increase if the quality of human resources is still low. There fore, the governments have a program to fix the quality of human resources by creating ready-to-work graduates through Vocational High School. The social support is the factor to determine the job readiness which for it has a major role to influence someone's mindset. In this case, the social support comes from parents, friends and also teachers. The problems statement of this research is to find out the relation between the social support and the readiness of Vocational High School student to work. The objective of this research is to find out the relationship between the social support and the job readiness of Vocational High School students. The hypothesis of this research is that there is a positive relationship between the social support and the job readiness of Vocational High School students. The subjects of this research are 136 people, who are the students of Grade XII SMK Bhakti Mulia Wonogiri. The writer uses incidental sampling in this research. The method of the data collection is a quantitative approach with the measuring instrument of the social support and job radiness scale. While the data analysis uses the correlation of product moment, with the program of SPSS 15 for windows. Based on the data analysis, the results of this research are the correlation coefisien is 0,653; the significance is 0,000 (p<0,01). From the results above it can be concluded that there is a significant positive relation between the social support and the readiness of Vocational High School students. The effective contribution or the role of the social support with the job readiness is 42,6% and the 57,4% is influenced by another factor. The empiric average of the job readiness variable is 117,14, therefore this variable has high category. Besides, the empiric average of the social support variable is 126,46, and it is also hass high category.